Assessing the vulnerability of social-environmental systems - Eakin, Hallie; Luers, Amy (Annual Review of Environment and Resources, 2006)
In this review, we highlight new insights into the conceptualization of the vulnerability of social-environmental systems and identify critical points of convergence of what otherwise might be characterized as disparate fields of research. We argue that a diversity of approaches to studying vulnerability is necessary in order to address the full complexity of the concept and that the approaches are in large part complementary. An emerging consensus on the issues of critical importance to vulnerability reduction—including concerns of equity and social justice—and growing synergy among conceptual frameworks promise even greater relevancy and utility for decision makers in the near future. We synthesize the current literature with an outline of core assessment components and key questions to guide the trajectory of future research.